2020
DOI: 10.1101/2020.08.10.20171348
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Love during lockdown: findings from an online survey examining the impact of COVID-19 on the sexual practices of people living in Australia

Abstract: Introduction: Australia recorded its first case of COVID-19 in late January 2020. On 22 March 2020, amid increasing daily case numbers, the Australian Government implemented lockdown restrictions to help flatten the curve. Our study aimed to understand the impact of lockdown restrictions on sexual and reproductive health. Here we focus on sexual practices. Methods: An online survey was open from the 23 April 2020 to the 11 May 2020. Participants were recruited online via social media and other networks and we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…This is consistent with previous studies showing a reduction in casual sex during the national lockdown in March–April. 3 , 4 , 9 It is also important to note that about one-third of MSM reported no casual partners in May–August. HIV postexposure prophylaxis (PEP) prescriptions have been used as a proxy for high-risk practices and studies have shown that there was a significant reduction in PEP prescriptions after the lockdown around March in Australia, the United Kingdom and Spain, where countries have been badly affected by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with previous studies showing a reduction in casual sex during the national lockdown in March–April. 3 , 4 , 9 It is also important to note that about one-third of MSM reported no casual partners in May–August. HIV postexposure prophylaxis (PEP) prescriptions have been used as a proxy for high-risk practices and studies have shown that there was a significant reduction in PEP prescriptions after the lockdown around March in Australia, the United Kingdom and Spain, where countries have been badly affected by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, other studies have reported an increase in activities with no risk for HIV and STI, such as masturbation and cybersex during the COVID-19 pandemic. 3 , 18 The reduction in sexual risk can potentially lead to temporal reductions in HIV and other sexually transmitted infections (STI). 5 , 19 , 20 However, the severity of COVID-19 pandemic in some settings may cause interruptions in delaying and accessing HIV/STI testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 For HIV and other sexually transmitted infections (STIs), behavioral responses to COVID-19 have included major reductions in social contacts ("social distancing") that also entailed reductions in sexual activity ("sexual distancing"). [2][3][4] The pandemic also has interrupted the provision of clinical services for HIV/STIs. 5 One critical question is how these two phenomenadistancing that could decrease HIV/STI transmission, and service interruption that could increase transmissionwill impact the overall incidence of HIV and STIs immediately and in the post-COVID era.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, findings from another study of 979 working adults in Germany suggest that while positive affect was lower between March 2020 and May 2020 compared to December 2019 to March 2020, reports of positive affect were associated with higher levels of emotional support (Zacher & Rudolph, 2021). While receiving emotional support was inhibited for some individuals due to adhering to social distancing guidelines, recent evidence suggests these individuals found alternative ways, such as CMC, to maintain their current and create new social connections (Anderson & Vogels, 2020;Coombe et al, 2020). Particularly, the use of CMC provided users with the ability to (re)connect with old and new friends and increase their social capital (Chen & Li, 2017).…”
mentioning
confidence: 99%